KAJIAN PENYALURAN KREDIT USAHA RAKYAT (KUR) PERTANIAN PADA BANK BRI KANTOR CABANG TONDANO - Praiselia Amanda; Ribka M. Kumaat; Celsius Talumingan; Tommy F. Lolowang (Universitas Sam Ratulangi, 2015)
ABSTACT The objective of this research in to observe the realization of chanelling KUR Agriculture at Bank BRI Tondano Branch Offices. The research was conducted with data collecting taken from Bank BRI Tondano Branch Offices. The data is processed qualitative research methods presented in the form of charts and tables. Â The Research result indicate that the study of KUR Agricultural field at Bank BRI Tondano Branch Offices showed excellent improvement, but the socialization of KUR financing to farmers in rural areas is still lacking, so there are many farmers who are less familiar with the financing programmed government since 2007.